Hubungan Tingkat Pengetahuan Keterampilan Pengisian Partograf Pada Mahasiswi Prodi Kebidanan Fakultas Kesehatan Universitas Patria Artha - Surmayanti Sumaryanti; Fitriana Jufri P (Yayasan Jompa Research and Development, 2023)
One of the efforts that can be made to increase the knowledge and skills of midwives in helping deliveries is by using the partograph. The partograph is a tool for making clinical decisions, monitoring, evaluating and managing labor. The purpose of this study was to determine the relationship between the level of student knowledge about partographs and the practice of filling out partographs in midwifery Program study Fakultas Kesehatan, Patria Artha University. Method: Quantitative research with analytic survey method with a sample of 30 respondents. Data were analyzed using the Chi Square statistical test. Results: 54 respondents (52.4%) had good knowledge, 41 respondents (39.8%) had fairly good knowledge, and 8 respondents (7.8%) had poor knowledge. Conclusion: In the practice of filling out partographs, 52 respondents (50.5%) did not pass, and 51 respondents (49.5%) passed. With ∝=5%, a p-value (0.036) <0.05 is obtained, which means that there is a relationship between the level of student knowledge about the partograph and the practice of filling in the partograph.